Separación de células linfoides bovinas por centrifugación isopicnica. - Camacho de Viáfara, N.; Mariño de Peña, O.C.; Rueda de Clavijo, O.E. (Instituto Colombiano Agropecuario, 2018)
Ganadería bovina